(untitled) (Research, Society and Development, 2023)
Addressing the relationship between plants and religions of African origin refers to the cultural value in today’s society, the merger of understanding in the construction of stories and knowledge, which are transmitted through rituals and experiences in a Umbanda terreiro (a terreiro is a place of worship in Umbanda). This research aimed to analyze the ethnobotany of the Luz Divina de São Jorge terreiro. Semi-structured interviews were developed for the leaders of the terreiro, in which they used tables but also oral accounts to indicate the history of the terreiro, which plants were used in ritualistic, medicinal, culinary, mystical and energetic practices and their particularities. Thirty-nine species were described, in addition to the parts of the plants that were used and which Orixás or guides they were related to. Of the plants mentioned, 20 (51.28%) can be found in the backyard of the terreiro, while 19 (48.72%) are not in the terreiro, having to be acquired when necessary. Of the described plants, 24 (61.54%) were identified at the species level and 15 (38.46%) at the genus level. The plants can be used in: baths, blessing and attraction rituals ("passes", "firmezas"); mandalas; ritual songs; cleaning and exorcising rituals ("descarregos", "defumações", "varrimentos"). The forms of medicinal use described were: teas; roots; baths; smokings; saps; compresses and oils. The terreiro has a variety of plants both in its territory and in its ritualis. The religious knowledge in the researched terreiro is permeated with traditional and medicinal knowledge, being passed from generation to generation. Knowing and using plants is a daily task in the Umbanda routine, turning this religion also into a guardian of the vegetation and species cultivated in this environment.